Penegakan Hukum terhadap Tindak Pidana Pencucian Uang dalam Kasus Investasi Binomo demi Keadilan bagi Korban - Nugroho, Dryan; Firmansyah, Hery (Universitas Ekasakti, 2024)
The Tangerang District Court possesses the jurisdiction to examine and adjudicate Criminal Cases involving the Defendant Indra Kesuma, also known as Indra Kenz. The charges against Indra Kesuma include the intentional and unauthorized transmission, distribution, and accessibility of electronic documents and/or electronic information containing gambling content. On February 3, 2022, the Criminal Investigation Body of the Indonesian National Police (Bareskrim Polri) received multiple reports from the public who claimed to have been harmed by Indra Kesuma, with report number LP/B/0058/II/2022/SPKT/BARESKRIM. These reports allege violations of Article 45 paragraph (2) Jo. Article 27 paragraph (2) and/or Article 45 paragraph (1) of Law No. 19 of 2016, which pertains to Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE). Additionally, there are alleged violations of Article 3, Article 5, and Article 10 of Law No. 8 of 2010, which addresses the Prevention and Eradication of Money Laundering Criminal Acts (TPPU), as well as alleged violations of Article 378 Jo. Article 55 of the Criminal Code.